Transductional construction of a threonine-producing strain of Serratia marcescens. - Komatsubara, S (1979)
A threonine-producing strain of Serratia marcescens Sr41 was constructed according to the following process. Thr- strain E-60 was derived from strain HNr59 having constitutive levels of threonine-sensitive aspartokinase and homoserine dehydrogenase. Thr+ transductant T-570 was constructed from strain E-60 and phage grown on strain HNr21 having feedback-resistant threonine-sensitive aspartokinase and homoserine dehydrogenase. This transductant lacked both feedback inhibition and repression for the two enzymes. Thr- strain N-11 was derived from strain AECr174 lacking feedback inhibition and repression of lysine-sensitive aspartokinase. Subsequently, the threonine region of strain T-570 was transduced into strain N-11. One of the THR+ transductants, strain T-693, produced markedly high levels of the two aspartokinases and homoserine dehydrogenase, which were insensitive to feedback inhibition. This strain produced about 25 mg of threonine per ml in the medium containing sucrose and urea.